Family Communication and Subjective Academic Well-being Among Secondary School Students: The Mediating Roles of School Belonging and Meaningful Experiences - Yildirim, Murat; Batmaz, Hasan; Kurtulus, Emin; Yildirim-Kurtulus, Hacer (SAGE PUBLICATIONS LTD, 2025)
Family communication has significantly impacted children's well-being and potentially affects their academic outcomes. This study examined the mediating role of school belonging and meaningful school experiences in the relationships between family communication and subjective well-being in students. The study utilised an online survey with a cross-sectional research design involving 427 (Mage = 12.00; SD = 0.85) full-time secondary school students (55.3% girls) in Turkey. Findings revealed that family communication had a direct positive effect on school belonging and meaningful school experiences. School belonging and meaningful school experiences had direct positive effects on students' subjective well-being. Furthermore, the results showed that school belonging and meaningful school experiences mediated the relationship between family communication and students' subjective well-being. This suggests the need for interventions that promote school belonging and meaningful school experiences to support students' well-being and academic success throughout their educational lives.
Keywords: family communication; school belongingness; meaningful school experiences; student subjective well-being; secondary school students; PARENT-ADOLESCENT COMMUNICATION; MENTAL-HEALTH; POSITIVE PSYCHOLOGY; LIFE; MODEL; PERCEPTIONS; INVOLVEMENT; VALIDATION; MOTIVATION; SUPPORT; Education & Educational Research; Social Work